2022
DOI: 10.3390/polym14235281
|View full text |Cite
|
Sign up to set email alerts
|

Wear Analysis of Tibial Inserts Made of Highly Cross-Linked Polyethylene Supplemented with Dodecyl Gallate before and after Accelerated Aging

Abstract: The wear of the tibial insert is one of the primary factors leading to the failure of total knee arthroplasty. As materials age, their wear performance often degrades. Supplementing highly cross-linked polyethylene (HXLPE) with dodecyl gallate (DG) can improve the oxidation stability of tibial inserts for use in total knee arthroplasty (TKA). This study aimed to evaluate the wear resistance of HXLPE supplemented with DG (HXLPE-DG) tibial inserts before and after accelerated aging. HXLPE-DG tibial inserts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, recent studies have shown that a neutral alignment did not improve the clinical outcome or survival rate, and a tolerance of 3° varus to 3° valgus could not be considered a “safe zone” with modern personalized alignment strategies, especially for an updated prosthesis ( Tibbo et al, 2021 ; Schelker et al, 2022 ). A possible reason is considerable differences in the design of contemporary knee prostheses, which can affect the mechanical behavior and wear performance ( Asseln et al, 2021 ; Zhang et al, 2021 ; Su et al, 2022 ). Although advanced techniques, like personalized specific instrumentation, navigation systems, and robotic surgeries, have improved surgical precision and alignment accuracy, malalignment is still a common complication.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that a neutral alignment did not improve the clinical outcome or survival rate, and a tolerance of 3° varus to 3° valgus could not be considered a “safe zone” with modern personalized alignment strategies, especially for an updated prosthesis ( Tibbo et al, 2021 ; Schelker et al, 2022 ). A possible reason is considerable differences in the design of contemporary knee prostheses, which can affect the mechanical behavior and wear performance ( Asseln et al, 2021 ; Zhang et al, 2021 ; Su et al, 2022 ). Although advanced techniques, like personalized specific instrumentation, navigation systems, and robotic surgeries, have improved surgical precision and alignment accuracy, malalignment is still a common complication.…”
Section: Discussionmentioning
confidence: 99%